A fiducial-assisted strategy compatible with resolving small MFS transporter structures in multiple conformations using cryo-EM - Pujun Xie; Yan Li; Gaëlle Lamon; Huihui Kuang; Da-Neng Wang; Nathaniel J. Traaseth (Nature Communications)
Abstract Advancements in cryo-EM have stimulated a revolution in structural biology. Yet, for membrane proteins near the cryo-EM size threshold of approximately 40 kDa, including transporters and G-protein coupled receptors, the absence of distinguishable structural features makes image alignment and structure determination a significant challenge. Furthermore, resolving more than one protein conformation within a sample, a major advantage of cryo-EM, represents an even greater degree of difficulty. Here, we describe a strategy for introducing a rigid fiducial marker (BRIL domain) at the C-terminus of membrane transporters from the Major Facilitator Superfamily (MFS) with AlphaFold2. This approach involves fusion of the last transmembrane domain helix of the target protein with the first helix of BRIL through a short poly-alanine linker to promote helicity. Combining this strategy with a BRIL-specific Fab, we elucidated four cryo-EM structures of the 42 kDa Staphylococcus aureus transporter NorA, three of which were derived from a single sample corresponding to inward-open, inward-occluded, and occluded conformations. Hence, this fusion construct facilitated experiments to characterize the conformational landscape of NorA and validated our design to position the BRIL/antibody pair in an orientation that avoids steric clash with the transporter. The latter was enabled through AlphaFold2 predictions, which minimized guesswork and reduced the need for screening several constructs. We further validated the suitability of the method to three additional MFS transporters (GlpT, Bmr, and Blt), results that supported a rigid linker between the transporter and BRIL. The successful application to four MFS proteins, the largest family of secondary transporters in nature, and analysis of predicted structures for the family indicates this strategy will be a valuable tool for studying other MFS members using cryo-EM.